Maternal sensitivity, its relationship with child outcomes, and interventions that address it: a systematic literature review. Issue 2 (25th January 2020) - Deans, Carolyn L.
ABSTRACT: There is strong evidence that children of mothers with insecure attachment styles have poor outcome trajectories. Maternal sensitivity may be the behaviour which links mother and child attachment models. This would, therefore, be a natural target for treatment in attachment interventions. A systematic literature review was conducted to determine the body of knowledge regarding maternal sensitivity, with a focus on the evidence-base for maternal sensitivity measures and interventions. We searched the PsychINFO and Medline databases up to December 2016, for peer-reviewed journal articles with 'maternal sensitivity' in the subject heading, MeSH Terms or abstract fields. One thousand four hundred and fifteen articles were retrieved. Following removal of duplicates and non-relevant material, 687 articles reviewed and categorized. There is extensive research linking maternal sensitivity, attachment, and child outcomes. Far fewer articles exist of published maternal sensitivity measures or interventions. At present, the evidence-base for directly affecting attachment via maternal sensitivity interventions is equivocal.